Climate warming impacts on soil organic carbon fractions and aggregate stability in a Tibetan alpine meadow. (January 2018) - Guan, Song; An, Na; Zong, Ning; He, Yongtao; Shi, Peili; Zhang, Jinjing; He, Nianpeng
Abstract: Alpine meadows in the Tibetan Plateau contain a large amount of soil organic carbon (SOC), which is highly vulnerable to climate change and has thus been a research priority for scientists in recent decades. However, how climate warming influences the composition and stability of SOC remains unclear. In this study, a warming experiment (2010–2015) using open-top chambers was established (with unwarmed control [CK], winter warming [WW], and year-round warming [YW]) to investigate the effects of warming on the contents of SOC and its fractions, chemical composition of SOC, and water stability of aggregates in an alpine meadow located at the Damxung Grassland Station in the northern Tibetan Plateau. Experimental warming had no apparent effect ( p > 0.05) on SOC content (17.8 ± 1.96, 17.8 ± 1.13 and 17.8 ± 1.09 g kg −1 under CK, WW and YW, respectively) in the 0–20 cm soil layer. However, warming significantly ( p < 0.05) increased soil water-soluble organic carbon (C) content by 46.2% and 69.2%under WW and YW, respectively, and affected SOC chemical composition with decreasing phenol C (by 2.6% under WW, p > 0.05; and 8.4% under YW, p < 0.05) and increasing carboxyl C (by 11.6% under WW, p < 0.05; and 5.0% under YW, p > 0.05). Warming decreased ( p > 0.05) the proportions of macroaggregates (2–0.25 mm) and free microaggregates (0.25–0.053 mm), whereas warming significantly increased the proportion of non-aggregated silt- and clay-sized fractions (<0.053 mm) by 41.0% and 55.7% under WW and YW, respectively. The variation in the aggregate size distribution resulted in the decline of the mean weight diameter and geometric mean diameter of water-stable aggregates by 5.1% ( p > 0.05) and 8.5% ( p < 0.05) under WW and by 8.5% and 6.6% (both p < 0.05) under YW, respectively. Of importance, the organic C content in free microaggregates, which provides greater physical protection to stabilize SOC, decreased by 10.9% ( p > 0.05) under WW and by 22.4% ( p < 0.05) under YW. The organic C contents of particulate organic matter and silt- and clay-sized fractions inside free microaggregates also significantly decreased under YW by 49.4% and 16.9%, respectively. However, the organic C content in non-aggregated silt- and clay-sized fractions significantly increased under WW and YW by 52.9% and 46.8%, respectively. The results suggest that short-term climate warming did not affect total SOC stocks, whereas it had a positive effect on WSOC, carboxyl C and non-aggregated silt- and clay-associated C and exhibited a negative effect on phenol C, free microaggregates-associated C and water stability of aggregates. These variables may act as sensitive indicators of climate warming in the Tibetan alpine meadows, which will in turn affect grassland ecosystem C fluxes in response to further climate change. The findings of the present study help improve our understanding of the responses of terrestrial ecosystem C cycling to future climate change. Highlights: 5-year warming had no significant effect on soil organic carbon (SOC) content. Warming affected SOC composition with decreasing phenol C and increasing carboxyl C. Warming significantly increased soil water-soluble organic carbon content. Warming decreased organic carbon associated with free microaggregates. Warming enhanced non-aggregated silt+clay fractions and aggregates stability fell.